MOTIF DAN KEPUASAN JEMAAT HURIA KRISTEN BATAK PROTESTAN (HKBP) DENPASAR DALAM MENONTON FILM TOBA DREAMS PADA ACARA “NONTON BARENG” - Marpaung, Putri Ulpa; Suryawati, I Gusti Alit; Pradipta, Ade Devia (E-Jurnal Medium, 2019)
ABS TRACT   T his s tudy want to s ee th e motives and s atisfaction Huria K r i s ten B atak P r otestan ( HKBP)   Denpasar’s   c ongregation   o n   watching   t he   f il m   “T oba   Dreams”  i n   Nonton   B areng’s event. T h i s s tudy uses d escriptive q uantitative methods. T he media c onsumption motive as the r eference i n this s tudy i s t he motive p ut f orward by Dennis M cQ uail. T h i s s tudy found t hat the four motives according t o M cQ u ail c ould be s atisfied. T his i s evidenced by the v alue of each motive or s ought gratification ( gs) which i s s maller than t he v a l ue of e ach s atisfaction or gratification   obtained.   T here  are  two  m otives   t hat   a r e  s atisfied   beyond  the  o v erall   average sc ore, based on the r esults of the questionnaire s pread from 4 i ndicators used to measure, there are 2 i ndicators that have an average v alue greater than the overall motive ( 4.53), n amely i ndicators of motives of s elf-identity ( 4 , 63) as w e l l as motives for i ntegration a nd s ocial i nteraction ( 4.78). A nd there are 2 i n dicators that have an average v alue greater than overall s atisfaction ( 4.65) w hich i s an i ndicator o f s atisfaction on the m otive of s e l f-identity ( 4.82) as well as s atisfaction w i th the motives for i ntegration and s ocial i nteraction ( 4.85).